Spectrum Orders: Digital Science Fiction and the Corrected Present. - Sheldon, Rebekah (Science Fiction Studies, 2016)
This article examines the aesthetics of what Anthony Dunne calls "Hertzian space" or the electromagnetic flows that enable wireless communication devices through comparative attention to three contemporary transmedia universes: the BBC's Sherlock, SyFy's Alphas, and Fox's Touch. I argue that each of these shows uses the emerging conventions of neuro-atypicality in order to make visible and render as story the data streams whose omnipresence cannot be experienced as such by the human sensorium without first becoming meaningful. This need for translation from data to narrative disrupts a fantasy of effortless transduction. I contend that the difficulty is solved through the characters of Sherlock, Gary, and Jacob, who give us unmediated access to dataflows. By the same token, these characters intimate a new form of epistemic mastery and concomitant subjectivization.